A study of the vertical homogeneity of trace gases in East Asian continental outflow. (June 2022) - Chang, Chih-Yuan; Wang, Jia-Lin; Chen, Yen-Chen; Pan, Xiang-Xu; Chen, Wei-Nai; Lin, Ming-Ren; Ho, Yu-Jui; Chuang, Ming-Tung; Liu, Wen-Tzu; Chang, Chih-Chung
Abstract: East Asian continental outflows containing with pollutants may deteriorate air quality in the downwind region via long-range transport (LRT). In particular, cold fronts with high wind speeds generally promote the LRT of air pollutants to further downwind areas, including Taiwan. To gain an insightful understanding of the characteristics and vertical homogeneity of trace gases in East Asian continental outflows, as well as their relation with atmospheric meteorological conditions, whole air samples were collected above a cape at the northern tip of the island of Taiwan during frontal passages. Aerial samples were collected at multiple altitudes from the surface to a maximum height of 700 m with a multicopter sounding platform carrying a robotic whole air sampling device. Simultaneously, aerial meteorological variables of temperature and wind vector from near the surface to a maximum height of 1000 m were also measured during the whole air sampling periods. An array of 106 volatile organic compounds (VOCs) as well as CO, CO2, and CH4 were analyzed to characterize the air composition and vertical homogeneity of trace gases. The results revealed rather homogeneous vertical distributions of most VOCs, CO, CO2, and CH4 in the frontal passages, indicating well-mixed conditions of trace gases in the East Asian continental outflows. The strong wind shear and minimal temperature inversion associated with the frontal passage likely induced turbulence and increased vertical mixing. Furthermore, higher levels of species characteristic of the East Asian continent were observed from the surface up to hundreds of meters above the cape, revealing a strong inflow of polluted air masses from the East Asian continent brought by cold frontal passages. Graphical abstract: Image 1 Highlights: Cold fronts with high wind speeds promote East Asian continental outflows. Large wind variation and lack of temperature inversion increases vertical mixing. Vertical homogeneity of trace gases was observed in the frontal passages. The observed composition is the result of species experiencing atmospheric processes.